PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA SISWA SD 59 GAROTIN KAB. ENREKANG - Makhrajani Majid; Melda Meiresa; Sitti Amina; Milda Juwina; Hasra Hasra; Nopi Nopi; Khusnul Khatimah; Zuraidah Inara Gani (Media Literasi Indonesia, 2025)
Clean and Healthy Living Behavior is a fundamental aspect in efforts to improve public health standards. The implementation of PHBS in school environments serves a strategic purpose: to empower students, educators, and the surrounding community with the knowledge, willingness, and ability to adopt healthy behaviors, while contributing to the creation of a clean and healthy school environment. A PHBS education program was conducted at SD 59 Garotin with the aim of enhancing sixth-grade students’ knowledge and awareness regarding the importance of maintaining personal health, particularly through proper handwashing practices. The methods employed in this activity included lectures, interactive discussions, and hands-on practice. The program took place on February 11, 2025, and involved active participation from the students. Evaluation results indicated a significant improvement in students’ understanding of PHBS concepts and practices following the intervention.. In conclusion, the education program implemented at SD 59 Garotin successfully improved sixth-grade students' health literacy, especially in the area of hand hygiene. As a follow-up, it is recommended that similar programs be implemented in other schools to broaden the reach and positive impact on school-age children’s health behaviors